Optimized hydrogen sensing characteristic of Pd/ZnO nanoparticles based Schottky diode on glass substrate - Chandra L.; Sahu P.K.; Dwivedi R.; Mishra V.N. (My University, 2025)
The present work deals with the development of the Pd/ZnO naoparticles based sensor for detection of hydrogen (H2) gas at relatively low temperature (75-110 °C). Pd/ZnO Schottky diode was fabricated by ZnO nanoparticles based thin film on glass substrate using sol-gel spin coating technique. These ZnO nanoparticles have been characterized by x-ray diffraction (XRD), atomic force microscopy (AFM), energy dispersive x-ray spectroscope (EDS), and field emission scanning electron microscope (FE-SEM) which reveals the ZnO film having particles size in the range of ∼25 to ∼110 nm with ∼52.73 nm surface roughness. Gas dependent diode parameters such as barrier height and ideality factor have been evaluated upon exposure of H2 gas concentration in the range from 200-2000 ppm over the temperature range from 75 to 110 °C. The sensitivity of the Pd/ZnO sensor has been studied in terms of change in diode forward current upon exposure to H2 gas. Experimental result shows the optimized sensitivity ∼246.22% for H2 concentration of 2000 ppm at temperature 90 °C. The hydrogen sensing mechanism has been explained by surface and subsurface adsorption of H2 molecules on Pd surface; subsequently, dissociation of H2 molecules into H + H atoms and diffusion to trap sites (oxygen ions) available on ZnO surface, resulting in formation of dipole moments at Pd/ZnO interface. The variation in the sensitivity, response and recovery time with temperature of Pd/ZnO sensor has also been studied. © 2017 IOP Publishing Ltd.